Patients satifaction towards healthcare services and its associated factors among patients attending the busiest government clinic in Pahang - Md Nor, Mohd Zamir; Said, Abdul Hadi; Che' Man, Mohamad; Yusof, Muhammad Zubir (Academy of Family Physicians of Malaysia (AFPM), 2023)
Introduction: Patient satisfaction is widely used to monitor the quality of health care services. A signicant patient load may inuence health care services and patient satisfaction.